Integrated Transcriptomic and Metabolic Analyses Highlight Key Pathways Involved in the Somatic Embryogenesis of Picea mongolica - Jinling Dai; Shengli Zhang; Yu’e Bai (Plants)
In the severe environment of Hunshandake Sandy Land, the uncommon and indigenous Chinese tree species Picea mongolica is an important biological component. Conventional seed propagation in P. mongolica is constrained by low germination rates, prolonged breeding cycles, and hybrid offspring genetic instability, limiting efficient varietal improvement. In contrast, somatic embryogenesis (SE) offers superior propagation efficiency, exceptional germination synchrony, and strict genetic fidelity, enabling rapid mass production of elite regenerants. However, SE in P. mongolica is hampered by severe genotype dependence, poor mature embryo induction rates, and loss of embryogenic potential during long-term cultures, restricting the production of high-quality seedlings. In this study, we aimed to analyze the transcriptome and metabolome of three crucial phases of SE: mature somatic embryos (MSEs), globular somatic embryos (GSEs), and embryogenic calli (EC). Numerous differentially expressed genes (DEGs) were found, especially in pathways linked to ribosomal functions, flavonoid biosynthesis, and the metabolism of starch and sucrose. Additionally, 141 differentially accumulated metabolites (DAMs) belonging to flavonoids, organic acids, carbohydrates, lipids, amino acids, and other metabolites were identified. An integrated study of metabolomic and transcriptome data indicated considerable enrichment of DEGs and DAMs in starch and sucrose metabolism, as well as phenylpropanoid biosynthesis pathways, all of which are required for somatic embryo start and development. This study revealed a number of metabolites and genes linked with SE, offering important insights into the molecular mechanisms driving SE in P. mongolica and laying the groundwork for the development of an efficient SE system.